Taken-for-granted assumptions about the clinical experience of newly graduated registered nurses from their pre-registration paid employment: A narrative inquiry. (September 2016) - Law, Yee-shui Bernice; Chan, E. Angela
Abstract: Paid employment within clinical setting, such as externships for undergraduate student, are used locally and globally to better prepare and retain new graduates for actual practice and facilitate their transition into becoming registered nurses. However, the influence of paid employment on the post-registration experience of such nurses remains unclear. Through the use of narrative inquiry, this study explores how the experience of pre-registration paid employment shapes the post-registration experience of newly graduated registered nurses. Repeated individual interviews were conducted with 18 new graduates, and focus group interviews were conducted with 11 preceptors and 10 stakeholders recruited from 8 public hospitals in Hong Kong. The data were subjected to narrative and paradigmatic analyses. Taken-for-granted assumptions about the knowledge and performance of graduates who worked in the same unit for their undergraduate paid work experience were uncovered. These assumptions affected the quantity and quality of support and time that other senior nurses provided to these graduates for their further development into competent nurses and patient advocates, which could have implications for patient safety. It is our hope that this narrative inquiry will heighten awareness of taken-for-granted assumptions, so as to help graduates transition to their new role and provide quality patient care.